1985
DOI: 10.1177/109019818501200205
|View full text |Cite
|
Sign up to set email alerts
|

A Health Belief Model Approach to Adolescents' Fertility Control: Some Pilot Program Findings

Abstract: We report initial findings from a community-based intervention intended to strengthen unmarried teenagers' fertility control behaviors (i.e., abstinence or consistent contraceptive usage). The Health Belief Model (HBM) was used as a conceptual framework for developing curriculum materials and for evaluating a 15-hour educational program targeted at 13- to 17-year-olds of both genders. Interview data pertaining to sexual and contraceptive perceptions, knowledge, and behaviors were collected three times in a no-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 10 publications
2
38
1
Order By: Relevance
“…[17] HBM was one of the first models used to predict and explain variations in contraceptive behavior among women. [18,19] Regarding the distribution of perception of susceptibility of using contraceptives at baseline, first post-test and second post-test, the current study revealed that there was no difference during the study period (see Table 1). These findings are supported by Baa et al [20] who studied "the perceptions of susceptibility to pregnancy among U.S. women obtaining abortions in Texas, one in a large town in a rural area of Washington State.…”
Section: Discussionmentioning
confidence: 65%
“…[17] HBM was one of the first models used to predict and explain variations in contraceptive behavior among women. [18,19] Regarding the distribution of perception of susceptibility of using contraceptives at baseline, first post-test and second post-test, the current study revealed that there was no difference during the study period (see Table 1). These findings are supported by Baa et al [20] who studied "the perceptions of susceptibility to pregnancy among U.S. women obtaining abortions in Texas, one in a large town in a rural area of Washington State.…”
Section: Discussionmentioning
confidence: 65%
“…A pilot study based on this framework proved effective in improving: beliefs about contraception, sexual knowledge, and effective contraceptive behavior among adolescents participating in a 15-hour educational program. 24 Simon and Das recommend the use of the HBM in conducting needs assessments for sexually transmitted disease education.25 However, they caution against the use of single-item measures of HBM concepts, suggesting the use of multiple items to measure each dimension of the model.…”
Section: Purpose Of the Studymentioning
confidence: 98%
“…Given the limited life experiences of an adolescent, they often demonstrate deficits in these social and assertive skills (Hagenhoff et al, 1987). Research has demonstrated that these skill deficits can be ameliorated through the use of behavior modification techniques such as role play and reinforcement (Eisen, Zellman, & McAlister, 1985). Although these programs are often successful in remediating the targeted personality characteristic (i.e., low self-esteem), they do not account for any change in the rate of teen pregnancy among participants (Stafford, 1989).…”
Section: Contraceptive Practices Among Teenage Girlsmentioning
confidence: 98%